Reaction of Rat Subcutaneous Connective Tissue to Resin Composites Polymerized with Different Light Curing Units and Different Lightening Methods. (14th June 2012) - Feiz, Atiyeh; Arbabzadeh Zavareh, Farahnaz; Mohammad Razavi, Seyed; Badrian, Hamid; Dolatyar, Sepideh; Vajihi, Mansoureh
Abstract : The aim of the study was to determine and compare the reaction of rat subcutaneous connective tissue to resin composites polymerized with different lights curing and lightening methods. In this in vivo study, 20 mature Wister Albino rats were used. The composite discs, 4 mm in diameter and 2 mm thick, were cured by QTH or LED light curing units with 4 different lightning methods (full power QTH, full power LED, pulse LED, and ramp LED). Five resin composite discs were implanted in each rat, so that 4 of 5 discs for implantation of cured composite discs differently and central one as control without implantation. After sacrificing at 7, 14, 30, and 60 days the inflammatory grade, fibrosis, and necrosis were determined. Freedman and Cochran tests were used to analyze the data using SPSS software ver. 15. The results of the study showed significant differences in inflammation grade and fibrosis among control group and 4 experimental groups at day 14 (P < 0.05 ). In necrosis, there was no significant difference among 4 groups in different times (P > 0.05 ). In conclusion, neither the type of light curing units (LED or QTH) nor the lightening methods can affect the grade of inflammatory reaction.